Sosialisasi Penerimaan Peserta Didik Baru dengan Pendekatan Manajemen Humas - Mohamad Muspawi; Gustriana Rindhi (Universitas Batanghari Jambi, 2019)
Describing the public relations strategy in carrying out activities to receive new students in SMA 7 Merangin is the purpose of this study, as well as about the factors and constraints when conducting socialization of the acceptance of new students. The nature of this research is qualitative research using case study research. The object of research is Merangin 7 Public High School with the Principal and Deputy Principal, especially in the field of Public Relations, as well as representatives of students of class X, XI, XII as the subjects of this study. Retrieval of data using observation techniques, interviewing, and documenting which is then followed by reducing the data that has been obtained following the presentation and verification so that conclusions can finally be drawn. In addition, the Triangulation technique is also used to test the validity of the data that has been obtained from this study. As for the results of this study: (1) the Public Relations Program of Merangin 7 Public High School has been well structured, but there is no surefire strategy in accepting new students; (2) Techniques in implementing the school public relations management strategy, namely school publications through the installation of banners / billboards, outreach, and through social media; (3) The implementation of the Public Relations 7 Merangin Public Relations management strategy has not been fully achieved, there are strategies that are not implemented, namely socialization; (4) The limiting factors are time and lack of human resources and the background of the school which was originally a private school